Unraveling the effect of the combination of modified atmosphere packaging and ε-polylysine on the physicochemical properties and bacterial community of greater amberjack (Seriola dumerili) - Wang, Di; Li, Xupeng; Yang, Xianqing; Chen, Shengjun; Li, Laihao; Wang, Yueqi; Pan, Chuang; Zhao, Yongqiang (Frontiers in Nutrition, 2022)
The combined effect of ε-polylysine (PL) and modified atmosphere packaging (MAP; 60% CO2/40% N2) on the bacterial community of greater amberjack fillets and their physicochemical properties were evaluated at 4 °C. The total viable counts (TVC), psychrotrophic bacterial count, sensory index, texture analysis, and total volatile basic nitrogen (TVB-N) revealed that PL, MAP, and MAP+PL treatment delayed the deterioration of greater amberjack fillets. These treatment groups also showed decreased accumulation of biogenic amines. High-throughput 16S rRNA gene sequencing results indicated that these treatments suppressed the growth of Pseudomonas in greater amberjack fillets. Furthermore, the MAP+PL treatment group was observed to be more effective than the PL and MAP groups, extending the shelf-life of greater amberjack fillets by 6 days. This investigation showed that the combination of PL and MAP has the potential to retain the quality and extend the shelf life of greater amberjack.